Using MRI to detect and differentiate calcium oxalate and calcium hydroxyapatite crystals in air-bubble-free phantom. Issue 8 (December 2015) - Mustafi, Devkumar; Fan, Xiaobing; Peng, Bo; Foxley, Sean; Palgen, Jeremy; Newstead, Gillian M.
Highlights: Investigated calcium oxalate and hydroxyapatite crystals in air bubble free phantom. These two crystals are commonly associated with breast benign and malignant lesions. Calcium hydroxyapatite crystal has stronger susceptibility, causing blooming artifacts. Susceptibility effects are emphasized by the bright ring around crystals. MRI may provide useful information regarding breast microcalcifications. Abstract: Calcium oxalate (CaOX) crystals and calcium hydroxyapatite (CaHA) crystals were commonly associated with breast benign and malignant lesions, respectively. In this research, CaOX (n = 6) and CaHA (n = 6) crystals in air-bubble-free agarose phantom were studied and characterized by using MRI at 9.4 T scanner. Calcium micro-crystals, with sizes that ranged from 200 to 500 µm, were made with either 99% pure CaOX or CaHA powder and embedded in agar to mimic the dimensions and calcium content of breast microcalcifications in vivo. MRI data were acquired with high spatial resolution T2 -weighted (T2W) images and gradient echo images with five different echo times (TEs). The crystal areas were determined by setting the threshold relative to agarose signal. The ratio of crystal areas was calculated by the measurements from gradient echo images divided by T2W images. Then the ratios as a function of TE were fitted with the radical function. The results showed that the blooming artifacts due to magnetic susceptibility between agar and CaHA crystals were more than twice as large as the susceptibility in CaOX crystals (p < 0.05). In addition, larger bright rings were observed on gradient echo images around CaHA crystals compared to CaOX crystals. Our results suggest that MRI may provide useful information regarding breast microcalcifications by evaluating the apparent area of crystal ratios obtained between gradient echo and T2W images.